2023
DOI: 10.32604/csse.2023.031008
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Fish Images Classification and Localization using Transfer Learning and Localization Aware CNN Architecture

Abstract: Building an automatic fish recognition and detection system for largescale fish classes is helpful for marine researchers and marine scientists because there are large numbers of fish species. However, it is quite difficult to build such systems owing to the lack of data imbalance problems and large number of classes. To solve these issues, we propose a transfer learning-based technique in which we use Efficient-Net, which is pre-trained on ImageNet dataset and fine-tuned on QuT Fish Database, which is a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…The integration of data derived from UAVs, which have already been widely used in land and sea applications [59][60][61][62], can provide a wealth of data for managing fish farms. By utilizing cameras, sensors, and other instruments, drones can capture high-resolution images and data on various important parameters for fish farm management such as water quality, fish health and behavior, farm infrastructure, and environmental conditions [63][64][65][66]. Finally, incorporating sea surface current data from remote sensing and numerical models can provide valuable information on the direction, speed, and variability of the currents.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of data derived from UAVs, which have already been widely used in land and sea applications [59][60][61][62], can provide a wealth of data for managing fish farms. By utilizing cameras, sensors, and other instruments, drones can capture high-resolution images and data on various important parameters for fish farm management such as water quality, fish health and behavior, farm infrastructure, and environmental conditions [63][64][65][66]. Finally, incorporating sea surface current data from remote sensing and numerical models can provide valuable information on the direction, speed, and variability of the currents.…”
Section: Discussionmentioning
confidence: 99%
“…A transfer learning based pre-trained model on ImageNet was used to improve the classification performance. In the study, a CNN-based architecture was studied [15]. For the categorization of fish images, Aziz et al suggested a Deep Learning Artificial Neural Network (DLANN) model with a cutting-edge optimization method.…”
Section: Methodsmentioning
confidence: 99%
“…The empirical results In recent years, the rise of deep learning has revolutionized the field of churn prediction. Ahmed et al [14] proposed a model, called TL-DeepE, for churn prediction. This model employed the principle of Transfer Learning and Ensemble-based Meta-Classification.…”
Section: Related Workmentioning
confidence: 99%